Awareness of hypertension and its impact on blood pressure control among elderly nigerians: report from the Ibadan study of aging - Raji, Yemi Raheem (Pan Afr Med J, 2017)
INTRODUCTION: Hypertension is highly prevalent among the elderly. Its awareness has a direct influence on control through drug adherence. Earlier studies have shown that awareness of hypertension is low among sub-Saharan African populations but only a few studies have looked at the prevalence and awareness of hypertension among the elderly. METHODS: The Ibadan Study of Ageing is a longitudinal cohort study of the mental and physical health status as well as the functioning of elderly persons residing in the Yoruba-speaking areas of Nigeria. Study was conducted in multiple waves from 2003/2004 to 2009. This report is based on the sample studied in 2007 (N = 1469). Respondents, aged ≥ 65 years, were assessed for the presence of hypertension, its awareness, receipt of and adherence to medication for the condition, and effectiveness of treatment on the control of blood pressure. Blood pressure was measured with the use of digital monitors (Omron MS - 2 Basic Model). Awareness of the diagnosis of hypertension was ascertained by self-reports. We explored social, economic, demographic and clinical correlates of the presence of hypertension, its awareness and control using multiple logistic regression analyses. RESULTS: The sample was composed of 809 (55.1%) females and 666 (44.9%) males. The mean age of the participants was 76.9 ± 8.4 years. Hypertension (defined as previous diagnosis by a health provider or a measured blood pressure higher than or equal to 140/90 mm Hg) was recorded in 973 (62.2%) participants, with females having a prevalence of 61.4% and males that of 70.1%. Other than female gender, residing in urban/semi urban areas and being overweight or obesity were associated with the occurrence of hypertension. Among those assessed to have hypertension, 78% were not previously aware of its presence. Factors independently associated with lack of awareness of hypertension included low socioeconomic class (OR 8.21, 95% CI 3.72-18.11, P < 0.001), and BMI >25kg/m(2) (OR 3.11, 95% CI 1.36-7.09, P < 0.009). Among those who were aware of the presence of hypertension and were on treatment, 77.3% still had uncontrolled hypertension. Only obesity or overweight (OR 5.56, 95% CI 1.35 - 22.83, P < 0.016) was independently associated with poor blood pressure control. CONCLUSION: The prevalence of hypertension among elderly Nigerians is high and those affected are often not aware of having the condition. Only a minority of those who receive treatment for the condition have adequate blood pressure control. The findings highlight the need for improved healthcare for the growing population of elderly persons, with particular attention to early detection and effective control of the condition.